An Integrated Operations Management System for Enhancing Administrative Efficiency in Ghana's District Assemblies - Brown, Philip; Bankas, Edem Kwedzo (Informatics and Software Engineering, 2024)
The COVID-19 pandemic, driven by the SARS-CoV-2 virus, necessitated an unprecedented shift to remote work, revealing critical gaps in digital infrastructures capable of maintaining organizational operations. This challenge was particularly pronounced in district assemblies in Ghana, where traditional, paper-based workflows impeded the transition to remote environments, heightening operational vulnerabilities. Despite the World Health Organization (WHO) downgrading COVID-19 as a Public Health Emergency of International Concern (PHEIC), the global ramifications of the virus and potential for future pandemics underscore the need for resilient, adaptable digital solutions. This paper presents an online integrated business operation management system tailored for district assemblies in Ghana. The system was developed using the Rapid Application Development (RAD) methodology, facilitating rapid, iterative deployment and user-centric design. Technologies such as HTML, CSS, and PHP were utilized for the front-end, while MySQL ensured secure and efficient back-end data management. The approach helped to digitize core administrative processes and transition from paper-based operations to streamlined electronic workflows. The implemented system successfully digitalized essential administrative workflows, improving operational continuity and efficiency. By replacing conventional procedures with robust electronic processes, the system provides a sustainable framework for enhanced functionality in public sector management. Furthermore, it strengthens organizational preparedness for future disruptions, ensuring resilience in remote and hybrid work contexts. The scope of this research is limited to district assemblies in Ghana, which may constrain the generalizability of the findings to other administrative contexts or geographical regions. Further studies could explore customization for broader governmental structures and assess long-term impacts on service delivery and user satisfaction. This paper presents a novel application of digital transformation principles within the public sector, addressing a critical gap in e-governance solutions for district assemblies in Ghana. By integrating user-focused design and scalable technology, the proposed system not only meets current administrative demands but also positions district assemblies for enhanced functionality and resilience in the face of future challenges.